Trends in Industrial Specialization and Development Dynamics in the Russian Regions - Grebenkin, Igor Vladimirovich (Economy of Regions, 2020)
Industrial specialization is one of the main elements characterizing and systemizing the economy that in many ways defines the regional development’s level and dynamics. The study discusses the main features of industrial specialization in the context of the need to assess structural factors and pro spects for regional development. The research methodology is based on developing the concept of diversified space and involves the analysis of statistical data reflecting the nature and trends of industrial development in the regions. Regional specialization is characterized as a separate phenomenon, assessed in relationship with close categories. Additionally, the paper specifies the place of industrial specialization among the factors of regional development. I describe the features and limitations of medium-term research of industrial specialization in Russian conditions. Then I assess the level and medium-term trends in the industrial specialization of the Russian regions. Industrial specialization is measured for the period from 2005 to 2017 based on official statistical data on the employment aggregated by sector and region. I applied a statistical indicator based on the adapted Spearman’s coefficient for studying the main characteristics of the relationship between specialization and the regional development’s parameters. The conducted analysis has identified the stable groups of regions with significant trends in the industrial specialization’s level. The relationship between the growth rates of regional manufacturing industry, the level and dynamics of relative specialization in various specifications has been empirically studied. In the majority of the Russian regions, the level of relative specialization was positively related with the dynamics of industrial development. Growing industrial specialization could help achieve faster and more stable economic growth. The results can be used in theoretical and empirical studies of regional development, including investment policy. The ambiguity of some results substantiates the directions for further research of various features of specialization in Russian regions: the multidimensionality of measurement, directions of evolution depending on regional potential, spatial and temporal continuity of specialization.